1998
DOI: 10.1076/phbi.36.4.280.4580
|View full text |Cite
|
Sign up to set email alerts
|

Sedative Effect of Walnut Leaf Extract and Juglone, an Isolated Constituent

Abstract: Sedative activity of Juglans regia L. (Juglandaceae) chloroform extract and of one of its isolated constituents was evaluated in mice. Dry chloroform extract and juglone, orally administered at 6.5 mg/kg and 0.125 mg/kg, respectively, induced marked sedation as measured by two tests (actimeter and sleep potentiation), compared with controls (diazepam, 2 mg/kg, per os). A separation method of juglone from chloroform extract was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 6 publications
0
34
0
1
Order By: Relevance
“…As dried leaves were used, juglone was not detected in any extract, which is in accordance with Wichtl and Anton (1999). Gîrzu et al (1998) have reported the isolation of juglone from a chloroformic extract of fresh walnut leaves. In the present work it was possible to detect this compound only in the chloroformic extract from a fresh sample (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As dried leaves were used, juglone was not detected in any extract, which is in accordance with Wichtl and Anton (1999). Gîrzu et al (1998) have reported the isolation of juglone from a chloroformic extract of fresh walnut leaves. In the present work it was possible to detect this compound only in the chloroformic extract from a fresh sample (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Walnut (Juglans regia L.) leaf has been widely used in folk medicine for treatment of venous insufficiency and haemorrhoidal symptomatology, and for its antidiarrheic, antihelmintic, depurative and astringent properties (Bruneton, 1993;Van Hellemont, 1986;Wichtl & Anton, 1999). Keratolytic, antifungal, hypoglycaemic, hypotensive, anti-scrofulous and sedative activities have also been described (Gîrzu et al, 1998;Valnet, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Juglone (5-hydroxy-1,4-naphthoquinone) is known as being the characteristic compound of Juglans spp. and is reported to occur in fresh walnut leaves (Bruneton, 1993;Gîrzu et al, 1998;Solar et al, 2006;Wichtl & Anton, 1999). Nevertheless, because of polymerization phenomena, juglone only occurs in dry leaves at vestigial amounts (Wichtl & Anton, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Walnut leaves are considered a source of healthcare compounds, and have been widely used in traditional medicine for he treatment of skin inflammation, venous insufficiency, hyperhidrosis haemorrhoidal symptomatology and ulcers, and for its antidiarrheic, antihelmintic, depurative, antiseptic, antibacterial, astringent, antioxidants and chemopreventive properties (Alkhawajah, 1997;Bruneton, 1993Bruneton, , 1999Carvalho et al, 2010;Van Hellemont, 1986;Wichtl & Anton, 1999). Keratolytic, antifungal, hypoglycaemic, hypotensive, anti-scrofulous and sedative activities have also been described (Gîrzu et al, 1998;Valnet, 1992).…”
Section: Introductionmentioning
confidence: 99%